Iron Metabolism in the Anaemia of Chronic Renal Failure. Effects of Dialysis and of Pareuteral Iron. Issue 5664 (26th July 1969) - Carter, R. A.; Hawkins, J. B.; Robinson, B. H. B.
Abstract : Serial studies of iron transport in patients on maintenance dialysis showed normal or raised values in almost all subjects and a transient increase soon after the start of dialysis in three. These patients, who were seldom or never transfused, had low serum iron levels and normal iron-binding capacity with low saturation. Iron transport was substantially increased by parenteral iron-dextran treatment. Tracer studies showed good iron utilization, with transport to the marrow rather than to the liver. In these circumstances iron therapy is safe and beneficial, and a useful rise in red cell mass was shown to result from it. The packed cell volume was found to be a valid index of red cell mass in these patients. Red cell loss in the dialysers was insufficient to account for the observed reduction in red cell survival.